PEMANFAATAN HASIL ASESMEN NASIONAL DALAM PROGRAM PENINGKATAN MUTU PENDIDIKAN DASAR DI DKI JAKARTA - Sodiyah Sanmarwi; Sri Sulastri (Jurnal Lingkar Mutu Pendidikan, 2022)
In carrying out the evaluation of the education system, the local government is accompanied by the UPT at the Director General of PAUD, Dikdas, and Dikmen. The objectives of this study are: obtaining educational problems that need to be prioritized and the root of the problem based on indicators in education report cards, and obtaining an activity program. The method used is a qualitative research method with a literature study approach. The conclusion of the study at the elementary school level was that there were educational problems in numeracy skills, character gaps, and a climate of diversity. At the junior high school level, the problems found were character gaps, and the APM for SMP/MTs/Package B/SMPLB. The root problems found at the elementary level are: character gaps between regions, religious and cultural tolerance, inclusive attitudes; support for religious and cultural equality, quality of learning, instructional leadership, school safety climate gaps, diversity climate gaps, inclusiveness climate, inclusiveness climate gaps, school community participation, proportion of use of school resources for quality improvement, use of ICT for budget management, and proportion utilization of the APBD for education. The root problems found at the junior high school level were: gender disparities, regional disparities, NER of students with disabilities, quality of learning, reflection and improvement of learning by teachers, instructional leadership, inclusiveness climate, participation of school residents, proportion of use of school resources for quality improvement, utilization of ICT for budget management, and the proportion of APBD utilization for education.